Identification positively affects the creativity of family business: The mediating role of family business support - He, Jianjia; Liu, Jusheng; Li, Tingting; Song, Liangrong (Frontiers in Psychology, 2022)
With the arbitrariness of family business decision-making and the complexity of interests become increasingly prominent, the transformation and innovation of family business are imminent. Under the above background, via analysis of data from 259 valid questionnaires from more than 10 family businesses in China as a sample and with the help of the SPSS and AMOS, this study explored the impacts of identification on creativity of the family business as well as the mediating role of family business support by constructing a mediating model. The results show that the employee's identification has a positive impact on the creativity of the family business. Besides, identification has a positive impact on family business support and family business support has a partial mediating role between identification and family business creativity. Especially, the emotional support doesn’t have a mediating role, whereas, the instrumental support has a complete mediating role between identification and family business creativity.